TINJAUAN NORMATIF TENTANG PENEGAKAN HUKUM TERHADAP PELAKU TINDAK PIDANA PERDAGANGAN SATWA LIAR MENURUT UNDANG-UNDANG NOMOR 5 TAHUN 1990 (Studi Kasus Di Indragiri Hilir) - Adi Putra, Bambang Sasmita; Fitri Wahyuni (JURNAL HUKUM DAS SOLLEN, 2024)
Indonesia is one of the most biodiverse countries in the world, with a wide variety of wildlife living in a variety of habitats, from tropical rainforests to oceans. Iconic wildlife includes iconic wildlife such as the Sumatran Tiger, Orangutan, Javan Rhino, Komodo dragon, and bird of paradise. However, this diversity is threatened by human activities such as poaching, illegal trade, deforestation and habitat destruction. To protect this biodiversity, law enforcement is needed against perpetrators of wildlife trade crimes, which are regulated in Law Number 5 of 1990. This research aims to provide an in-depth understanding of the dynamics of law enforcement for perpetrators of wildlife trade crimes and encourage improvements in existing legal practices. This research uses the normative legal research method, this research focuses on analyzing legal documents and sources. This method involves the study of various legal sources, such as laws, court decisions, contracts, legal theories, and experts' views. The results of this study show that the police have been quite good at investigating and arresting perpetrators, as well as continuing the legal process in accordance with Law No. 5 of 1990. The forest rangers are responsible for forest monitoring and community education on wildlife conservation, while the BKSDA identifies the condition of confiscated animals and is involved in conservation and education efforts..